2021
DOI: 10.2196/27884
|View full text |Cite
|
Sign up to set email alerts
|

The Effects of Exergaming on Sensory Reweighting and Mediolateral Stability of Women Aged Over 60: Usability Study

Abstract: Background Older adults tend to experience difficulties in switching quickly between various reliable sensory inputs, which ultimately may contribute to an increased risk of falls and injuries. Sideward falls are the most frequent cause of hip fractures among older adults. Recently, exergame programs have been confirmed as beneficial tools for enhancing postural control, which can reduce the risk of falls. However, studies to explore more precisely which mechanism of exergaming directly influences … Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 7 publications
(2 citation statements)
references
References 62 publications
0
2
0
Order By: Relevance
“…Among the internet-and game-based technologies used for exercise training, the Kinect motion sensor (Microsoft Corp) constitutes a high-potential approach; it provides a precise markerless, full-body 3D motion tracker with real-time feedback about user performance and enables users to virtually interact hands-free with a computer system without needing a remote controller [30][31][32][33][34][35]. Lozano-Quilis et al [36] demonstrated the effectiveness of RemoviEM, a Kinect-based system offering people with MS an intuitive and motivating way to perform weight transfer and upper limb coordination exercises.…”
Section: Introductionmentioning
confidence: 99%
“…Among the internet-and game-based technologies used for exercise training, the Kinect motion sensor (Microsoft Corp) constitutes a high-potential approach; it provides a precise markerless, full-body 3D motion tracker with real-time feedback about user performance and enables users to virtually interact hands-free with a computer system without needing a remote controller [30][31][32][33][34][35]. Lozano-Quilis et al [36] demonstrated the effectiveness of RemoviEM, a Kinect-based system offering people with MS an intuitive and motivating way to perform weight transfer and upper limb coordination exercises.…”
Section: Introductionmentioning
confidence: 99%
“…In this process, the visual, vestibular, and proprioceptive systems detect information on body motion from the external world, and the relative weights of each sensory system change depending on environmental conditions, known as sensory reweighting [1][2][3]. Maladaptation of sensory reweighting to sudden changes in environmental conditions could lead to postural instability, resulting in falls [4] and motion-sickness [5,6]. Numerous studies have demonstrated that the change in sensory weights, known as sensory reweighting dynamics, will differ depending on the nature of the subjects.…”
Section: Introductionmentioning
confidence: 99%